A tale of two rivers: development, destruction, and despair in Ongata Rongai, Kenya - Howland, Olivia (Frontiers in Public Health, 2023)
Introduction Ongata Rongai is a rapidly growing peri-urban space in Nairobi Metropolitan, Kenya. The last 10 years have seen exponential population growth and building development leading to overcrowding and pressure on water and environmental resources. This original research sheds light on interactions among humans, animals, and this rapidly changing urban environment. It is therefore a quintessentially One Health study. Methods Qualitative and ethnographically informed methods are employed to better understand the impact of rapid growth on the riparian environment and the effect of this on those who depend on it. The reflexive use of archival material and a historical ethnographic approach enabled in-depth narratives to address these issues within a longitudinal context, and the use of deliberate walking alongside visual methodologies and more traditional anthropological methods make this study novel both in terms of methodological approach and findings. Results This study finds that people cite high levels of pollution from solid waste and sewage have made the rivers almost unusable and a hazardous place for both humans and animals. Yet, in the past, these rivers played key roles in daily life. There is frustration with structural-level actors' moribund attitude to the environment. The poor health of the rivers and riparian environment leads to human and animal health challenges, increased pressure on water resources, and economic pressure due to a loss of livelihoods. Discussion The study contributes to what is currently a fairly small literature on urban riparian spaces globally, but one which is of growing and vital importance given the rapidly increasing percentage of humans who now reside in urban spaces. It contributes to WASH and urban clean water knowledge as well as One Health, public health, and urban growth narratives, and directly addresses challenges faced by SDG 6.